1969
DOI: 10.1126/science.164.3879.551
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Rich Apatite

Abstract: More than 25 atomic percent of aluminum can susbtitute for other cations in the structure of apatite [A(10)(XO(4)) (6)Z(2)]. Such a synthetic product was obtained by expelling volatile constituents (H(2)O and F) from morinite during thermal treatment. Infrared absorption spectra, chemical analysis, and x-ray powder diffraction demonstrate that the aluminum has two coordination numbers, and more than twice as much aluminum substitutes for calcium (A position) as for phosphorus (X position).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The acid resistance of Al-treated enamel has been attributed to the formation of well-defined, complex Al phosphates [Torell, 1954] and to the substitution of two Al atoms for three calcium atoms without loss o f phosphate in the hy droxyapatite lattice [McCann, 1969]. Several mineralogical investigations of apatites [Rodgers, 1924;McConnell, 1952;Fisher and McConnell, 1969;Trueman, 1966;McConnell. 1973] have reported the existence of apatites containing Al and theorized that Al can substitute for apatitic calcium, and perhaps phosphorus, since the structure of apatite is very tolerant with respect to modification by isomorphic substi tution.…”
Section: Discussionmentioning
confidence: 99%
“…The acid resistance of Al-treated enamel has been attributed to the formation of well-defined, complex Al phosphates [Torell, 1954] and to the substitution of two Al atoms for three calcium atoms without loss o f phosphate in the hy droxyapatite lattice [McCann, 1969]. Several mineralogical investigations of apatites [Rodgers, 1924;McConnell, 1952;Fisher and McConnell, 1969;Trueman, 1966;McConnell. 1973] have reported the existence of apatites containing Al and theorized that Al can substitute for apatitic calcium, and perhaps phosphorus, since the structure of apatite is very tolerant with respect to modification by isomorphic substi tution.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators [Adler and Csoban, 1948;Manly and Bibby, 1949;Kleber, 1985, 1986;Kleber and Putt, 1985;Christoffersen and Christoffersen, 1985;Matsuo ct al., 1987] have demon strated in vitro that Al reacts with intact enamel, powdered enamel, or synthetic apatite crystals, resulting in much less susceptibility to subsequent dissolution in acid. The acid re sistance o f Al-treatcd enamel is probably attributable to the formation o f very insoluble Al phosphate reaction products [Torell, 1954], Also mineralogists [Rodgers, 1924;McCon nell, 1952;Fisher and McConnell, 1969;Trueman, 1966;McConnell, 1973] have reported on the existence and for mation o f Al-substituted apatite. Thermodynamically, Al can readily displace Ca bound to phosphate in apatite [Mar tin, 1986] with the possible substitution of two Al atoms for three calcium atoms in the crystal lattice [McCann, 1969].…”
Section: Discussionmentioning
confidence: 99%
“…A most interesting situation is the substitution of AI for both Ca and P. Through heating of morinite, FISHER & MCCONNELL [62] found that something intermediate between Ca6AI4(P04)4(AI04)2F2 and CasAI2(P04)5(AI04)F2 formed with respect to its AI content. A most interesting situation is the substitution of AI for both Ca and P. Through heating of morinite, FISHER & MCCONNELL [62] found that something intermediate between Ca6AI4(P04)4(AI04)2F2 and CasAI2(P04)5(AI04)F2 formed with respect to its AI content.…”
Section: The Composition [Cdlo(p04)6f2] Is Exceptional In Showing Conmentioning
confidence: 99%
“…A most interesting situation is the substitution of AI for both Ca and P. Through heating of morinite, FISHER & MCCONNELL [62] found that something intermediate between Ca6AI4(P04)4(AI04)2F2 and CasAI2(P04)5(AI04)F2 formed with respect to its AI content. Although this might be supposed to create an ordering among the Al atoms of the structure, no evidence in support of this supposition was apparent [62]. However, it is noteworthy that the powder diffraction pattern was virtually indistinguishable from that of common apatites, both with respect to interplanar spacings and intensities, and thus gave no suggestion of a change of space group or significant change of a or c periodicities.…”
Section: The Composition [Cdlo(p04)6f2] Is Exceptional In Showing Conmentioning
confidence: 99%
See 1 more Smart Citation